PERFORMANCE OF A PIPE SLOW SAND FILTER (SSF-P) WITH DIFFERENCE HYDRAULIC HEADS ON FILTERING POLLUTANTS OF CRUMRUBBER PLANT LIQUID WASTE - Sigit Mujiharjo; Bosman Sidebang; Dedek Darmadi (BPFP Faperta UNIB, 2012)
Pipe slow sand filter (SSF-P) is an undertest slow sand filter (SSF) technology promising some advanatages. Purpose of this research is to test the performance of SSF-P with differencce level of hydraulic heads on reducing pollutants of crumrubber plant liquid waste. The SSF-P tested was a 5-inches-diameter, 50cm-long SSF-P and hydraulic heads applied were 10 cm, 20 cm and 30 cm. Result of test showed that SPL-P installed with all hydraulic heads tested were capable of reducing significant amount of pollutants, and with 10 cm head capable of producing filtrate with TSS, pH and NH3-N satisfying grade 1 (drinking) water.